"Not Just a Journal Club - It's Where the Magic Happens": Knowledge Mobilization through Co-Production for Health System Development in the Western Cape Province, South Africa - The Western Cape HPSR Journal Club Team (Kerman University of Medical Sciences, 2022)
BackgroundThe field of Health Policy and Systems Research (HPSR) views researchers as active participants in processes of knowledge mobilization, learning and action. Yet few studies examine how such processes are institutionalized or consider their health system or wider impacts. This paper aims to contribute insights by presenting a South African experience: the Western Cape (WC) HPSR Journal Club (JC).MethodsThe paper draws on collective reflection by its authorial team, who are managerial and academic JC participants; reflective discussions with a wider range of people; and external evaluation reports. The analysis has been validated through rounds of collective engagement among authors, and through comparison with the wider sets of data, documentation and international literature. It considers impacts using a framework drawn from the co-production literature. ResultsSince 2012, the JC has brought together provincial and local government health system managers and academics to discuss complex systems' and social science perspectives on health system development. The JC impacts encompass the trusting relationships (group micro-level) that have not only strengthened personal confidence and leadership skills (individual micro level), but also led to organizational impacts (meso level), such as practice and policy changes (practitioner organizations) and strengthened research and post-graduate teaching programs (academic organizations). Macro-societal impacts are, finally, judged likely to have resulted from new health system practices and policies and from academic post-graduate training activities. This set of impacts has been enabled by: the context of the JC; aspects of the JC design that underpin trusting relationships and mutual learning; the sustained participation of senior health system managers and academic managers who are able to translate new ideas into practice in their own organizational environments; and our individual and collective motivations - including the shared goal of health system development for social justice. Our challenges include risks and costs to ourselves, and the potential exclusion of challenging voices. ConclusionThe principles and practice of the JC approach, rather than the JC as a model, offer ideas for others wishing to mobilize knowledge for health system development through embedded and co production processes. It demonstrates the potential for productive human interactions to seed long lasting systemic change.